Dynamic Conditional Dependence for Turkey Earthquake Data: CD Vine Copula Approach - Karakaş, Ayse; Demir, Aslıhan; Çalik, Sinan (Bitlis Eren Üniversitesi, 2021)
The objective of this research was to use Turkey's major fault zones, which are located on fault lines, to describe the dependency structure. The current study also intended to show the dynamic structure of the conditional dependencies of the earthquake data in Turkey in terms of depth and magnitude, using the CD-vine copula method. Conditional dependence, also known as the CD-vine method, makes obtaining a complex dependency structure simpler. The current research uses 30 years of data from the Eastern Anatolian Fault line and the North Anatolian Fault line to describe the dynamic conditional dependency structure. As a consequence, this dependency structure is represented graphically and numerically in tables and graphs.